Adoption of robotic stroke rehabilitation into clinical settings: a qualitative descriptive analysis. Issue 4 (9th December 2020) - Lo, Kenneth; Stephenson, Matthew; Lockwood, Craig
ABSTRACT: Aim: Through this qualitative research of clinicians' perspectives and experiences, we seek to inform rehabilitation clinicians about the various aspects of adopting and integrating robotic stroke therapy into clinical settings. Methods: Semistructured interviews were conducted with individual clinical therapists to seek their perspectives on robotic stroke rehabilitation. From the data collected, qualitative descriptive analysis was used to inductively identify codes, categories and central themes. Results: The study examined various clinical, human behavioural and organizational factors of adopting robotic rehabilitation into clinical settings, and found that a preimplementation plan addressing various aspects (staff capacity, patient flow and transport, funding mechanism, location and physical space of the robotic devices) needed to be in place to ensure the successful adoption of robotic rehabilitation in a multidiscipline hospital. We also identified how to conduct robotic rehabilitation in terms of the patient inclusion criteria, therapy duration, and patient setup and supervision. We examined the attitudes and views of therapists and patients towards robotic rehabilitation, and presented the benefits that robotic training brought to these two user groups. Conclusion: Both therapist attitude and device benefit work together to shape the motivation of therapists to adopt robotics, and it would be worthwhile to have an adoption plan that actively generated positive attitudes and expounded the benefits of robotic training. Overall, an adoption plan needs to be well thought through and be all-encompassing, and we hope that the findings of this study can assist to inform this plan.